The bible, the qu'ran and science : the holy scriptures examined in the light of modern knowledge - Bucaille, Dr. Maurice ([S.l.] : Tahrike Tarsile Qur'an, 2003)
The Bible, the Qur'an, and Science is an objective study of the Old Testament, the Gospels and the Qur'an. This book seeks to spiritually unite by highlighting similarities in the texts. It sheds new light and dispels many preconceived ideas in separating what belongs to Revelation from what is the product of error or human interpretation.